5-Aminouracil synchronization of the cell cycle of Vicia Faba root tip meristems : a thesis presented in partial fulfilment of the requirements for the degree of Master of Science in Biology at Massey University - Butcher, Jennifer Ann (Massey University, 1977)
This study was undertaken to try and find how the thymine analogue 5-aminouracil induces cell synchrony in the cell cycle of plant root meristems. It has previously been used as a synchronizing agent without knowing its mode of action. The experiments confirmed the synchronization effect and that the removal of plants from 5AU stimulated the cells to divide. Results indicated that the late S and early G2 phases of the cell cycle were the most affected, with DNA synthesis continuing in the presence of 5AU at a reduced rate. The inhibition of division caused by 5AU could be reversed by other bases and mixtures. The G1 phase was found not to be affected by 5AU but it was postulated that cells in early G2 were slowed down or halted by the chemical. DNA density measurements were taken of nuclei treated continuously for varied times with 5AU, and these results confirmed a buildup of cells in the latter third of the S phase found by other workers. The presence of Feulgen-negative regions in chromatids of the 5AU treated tissue was noted and linked with possible interference in heterochromatin synthesis. The possibility of some enzyme function important in the final joining together of DNA units being interfered with by 5AU is also discussed. Suggestions are made for further possible avenues of work into DNA synthesis. The significance of cell cycle studies and their experimental design has recently been reconsidered and is mentioned in view of this work and other cell population studies.
Keywords: Meristem culture; Meristem